EPIDEMIOLOGICAL AND CLINICAL PROFILE OF STRONGYLOIDIASIS - EXPERIENCE FROM A TERTIARY CARE CENTRE - DUSI, RATNA HARIKA; BODA, SUBBARAYUDU; MOHAN, NITIN; CHEPURU, RAJYALAKSHMI; INDUGULA, JYOTHI PADMAJA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of the study was to study the clinical presentations, predisposing factors, and underlying conditions associated with Strongyloidiasis. Methods: A prospective observational study was conducted from 2018 to 2021on patients who presented with medical complaints in a tertiary care hospital, and 19 were diagnosed with strongyloidiasis by stool wet mount examination. Other relevant details were collected to analyze the risk factors. Results: A total of 19 cases were found positive for strongyloidiasis. Males 13 (68.4%) were more and females 6 (31.6%), and most of them were above 50 years age group (73.7%). Among the cases, respiratory symptoms (42.1%) were predominantly observed, followed by gastrointestinal (31.6%). Multiple predisposing factors such as chronic obstructive pulmonary disease, corticosteroid usage, TB, diabetes, alcohol, and asthma have been identified in strongyloidiasis cases. Peripheral eosinophilia is a frequent finding in the complete blood picture. Conclusions: Strongyloidiasis should be strongly suspected in every immune compromised patient presenting with gastrointestinal, respiratory manifestations, or peripheral eosinophilia, and asymptomatic immune competent patients with comorbid conditions.